PENERAPAN TERAPI SELF HYPNOSIS TERHADAP PENURUNAN BERAT BADAN PADA ANAK USIA SEKOLAH DI RT 06 / RW 02 KELURAHAN MAKASAR JAKARTA TIMUR - Indah Cahyasari (2022)
Obesity is one of the health problems that must be handled properly because it can affect individuals of all ages, from children to adults. Obesity occurs in school-age children because it can interfere with the health and body image of the child. Some interventions are believed to help lose weight in school-age children who are obese. Self Hypnosis therapy is one intervention that has been proven to be able to lose weight. The application of nursing care aims to determine the effectiveness of Self Hypnosis therapy on weight loss in school-age children who are obese. This intervention was given to two children in RT 06 / RW 02 and was carried out 2 times a week and was carried out for 3 weeks. The results of the implementation for 3 weeks showed that there was a weight loss of 1.6 kg in the first client and 2.0 kg in the second client. So it can be concluded that the intervention of Self Hypnosis therapy can affect weight loss of school-age children. Community nurses are expected to use Self Hypnosis therapy intervention as an intervention to lose weight in school-age children with obesity.